COST‐OFFSETS OF PRESCRIPTION DRUG EXPENDITURES: DATA ANALYSIS VIA A COPULA‐BASED BIVARIATE DYNAMIC HURDLE MODEL. (19th August 2013) - Deb, Partha; Trivedi, Pravin K.; Zimmer, David M.
SUMMARY In this paper, we estimate a copula‐based bivariate dynamic hurdle model of prescription drug and nondrug expenditures to test the cost‐offset hypothesis, which posits that increased expenditures on prescription drugs are offset by reductions in other nondrug expenditures. We apply the proposed methodology to data from the Medical Expenditure Panel Survey, which have the following features: (i) the observed bivariate outcomes are a mixture of zeros and continuously measured positives; (ii) both the zero and positive outcomes show state dependence and inter‐temporal interdependence; and (iii) the zeros and the positives display contemporaneous association. The point mass at zero is accommodated using a hurdle or a two‐part approach. The copula‐based approach to generating joint distributions is appealing because the contemporaneous association involves asymmetric dependence. The paper studies samples categorized by four health conditions: arthritis, diabetes, heart disease, and mental illness. There is evidence of greater than dollar‐for‐dollar cost‐offsets of expenditures on prescribed drugs for relatively low levels of spending on drugs and less than dollar‐for‐dollar cost‐offsets at higher levels of drug expenditures. Copyright © 2013 John Wiley & Sons, Ltd.